2014
DOI: 10.1093/eurheartj/ehu210
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, prospective, intercontinental evaluation of a bioresorbable polymer sirolimus-eluting coronary stent system: the CENTURY II (Clinical Evaluation of New Terumo Drug-Eluting Coronary Stent System in the Treatment of Patients with Coronary Artery Disease) trial

Abstract: AimThe aim of this study was to establish safety and efficacy of a new sirolimus-eluting stent with bioresorbable polymer, Ultimaster (BP-SES). Sirolimus-eluting stent with bioresorbable polymer was compared with everolimus-eluting, permanent polymer, Xience stent (PP-EES) in the frame of a CENTURY II clinical trial designed to make global clinical data compliant with regulatory requirements in Europe and Japan.Methods and resultsThe CENTURY II is a prospective, multicentre, randomized (1 : 1), single blind, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 29 publications
8
100
1
Order By: Relevance
“…Therefore, to the best of our knowledge this is the first study which evaluated the preclinical in-vivo and vascular tissue response to a novel generation SES and directly compared the healing with current golden standard, the everolimus eluting fluropolymer EES (Xience Pro). This is important in translation to already published clinical trials of similar technologies, which have shown non-inferior clinical and angiographic outcomes between novel generation SES and fluropolymer EES with regard to the incidence of major adverse cardiac events [5,10,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to the best of our knowledge this is the first study which evaluated the preclinical in-vivo and vascular tissue response to a novel generation SES and directly compared the healing with current golden standard, the everolimus eluting fluropolymer EES (Xience Pro). This is important in translation to already published clinical trials of similar technologies, which have shown non-inferior clinical and angiographic outcomes between novel generation SES and fluropolymer EES with regard to the incidence of major adverse cardiac events [5,10,21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that autonomously sirolimus and its derivatives (everolimus, zotarolimus) have similar effects on vascular response and clinical outcomes [4,5], therefore it has been postulated that the polymer and release kinetics were responsible for the negative tissue effect and clinical outcomes. The early generation SES consisted of non-erodible PEVA/PBMA polymers and thick strut profile stent platform which caused anaphylactic and inflammatory reactions, resulting in impaired vessel healing and ultimately adverse thrombotic events [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify whether the clinical outcomes of Ultimaster are affected by the stent diameter, we compared the results from the present study with those of the CENTURY II study, a pivotal study of Ultimaster stents that used stents with a diameter of 2.5-4.0 mm [14]. The CENTURY II study included an all-comer cohort (cohort B) and a cohort with more restrictive inclusion criteria compliant with Japanese regulations (cohort JR).…”
Section: Differences In Clinical Outcomes Among Different Vessel Diammentioning
confidence: 99%
“…24 Third, our meta-analysis was limited to FDA-approved new-generation DES and we did not include new biodegradable polymerbased DES. [36][37][38] …”
Section: Study Limitationsmentioning
confidence: 99%